A Safer, Simpler, Classic Intrafascial Supracervical Hysterectomy Technique - Kim, Dong Ho (Society of Laparoendoscopic Surgeons, 2005)
OBJECTIVES: Our aim is to introduce the technical aspects and advantages of a new classic intrafascial supracervical hysterectomy (CISH) technique over the conventional technique. METHODS: We performed a retrospective evaluation (Canadian Task Force classification II-2) of 200 women who underwent conventional CISH technique (100 cases), between March 2000 and September 2000, or the new CISH technique (100 cases) between May 2002 and November 2002. The charts of these 200 women were reviewed regarding patient characteristics, indications, uterine weight, estimated blood loss, operating time, and hemoglobin change. RESULTS: The women who underwent the new CISH had significantly shorter operating time as compared with operating time for the conventional method. Although no significant difference existed in the estimated blood loss, the hemoglobin change, which is an objective sign of blood loss, was significantly smaller using the new CISH technique than using the conventional CISH technique. CONCLUSIONS: The new CISH technique is safer, more convenient, faster, and results in less blood loss than the conventional technique, especially when the uterus is markedly enlarged by a large myoma, the ovarian ligament is too short, or the ovary and uterus are very closely adherent.